1981
DOI: 10.1161/01.cir.64.6.1089
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of nitroglycerin action: stenosis vasodilatation as a major component of the drug response.

Abstract: SUMMARY The effect of sublingual or intracoronary nitroglycerin (NTG) on luminal caliber in normal and diseased portions of epicardial coronary arteries was determined in 85 lesions from 57 typical patients with ischemic heart disease. Measurements were made from coronary angiograms, using a computer-assisted method and a carefully blinded protocol for analysis of the pre-and post-NTG angiograms. Luminal area in the "normal" portion of the diseased segment and at its maximum constriction and an estimate of flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
4

Year Published

1982
1982
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 444 publications
(72 citation statements)
references
References 40 publications
(2 reference statements)
6
62
0
4
Order By: Relevance
“…In contrast to traditional dogma regarding fixed stenoses, Brown et al 18 have shown that some coronary stenoses are responsive to vasoactive stimuli. This seems to be particularly true of eccentric lesions in which some portion of the circumference of the stenotic segment is not diseased.…”
Section: Resultsmentioning
confidence: 90%
“…In contrast to traditional dogma regarding fixed stenoses, Brown et al 18 have shown that some coronary stenoses are responsive to vasoactive stimuli. This seems to be particularly true of eccentric lesions in which some portion of the circumference of the stenotic segment is not diseased.…”
Section: Resultsmentioning
confidence: 90%
“…9 In normal subjects it is associated with 15% Control HGP A and intracoronary nitroglycerin despite increases in systemic pressure, heart rate, and double product that were virtually identical to those during the first handgrip test. This nitroglycerin dose has been previously shown to have no effect on systemic hemodynamics, including central venous pressure.20 21 Thus, constriction of severe coronary stenoses, and not increased double product, appears to be the principal mechanism for ischemic left ventricular dysfunction during isometric exercise.…”
Section: Discussionmentioning
confidence: 93%
“…The infusion was started at the onset of handgrip and continued at a uniform rate until the fourth minute; all measurements were repeated at between 4 and 4.5 min. This dose and rate of administration were selected because they approximated the concentration of nitroglycerin in coronary arterial blood (approximately 120 ng/ml after sublingual administration of 0.6 mg in a patient with 5 liters/min venous return), but was small enough in total dose that it would not effect systemic hemodynamics.20 21 After recovery from the second handgrip test, sublingual nitroglycerin (0.4 mg) was given in the absence of handgrip. Aortic, pulmo-*Stoelting, Inc., Chicago, IL.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrates produce an increase in coronary blood flow that is directly related to epicardial coronary artery dilation. [4][5][6] Transdermal nitroglycerin is widely used in the treatment of CAD. However, there is increasing evidence that sustained administration of nitrates can produce Although circulatory tolerance and cross tolerance in terms of blood pressure and heart rate have been demonstrated, limited data are available on nitrate cross tolerance in venous capacitance vessels, which are believed to be the site of predominant nitrate action?.…”
Section: Introductionmentioning
confidence: 99%